TIGA RUNGGU VILLAGE SIAM ORANGE FARMING BUSINESS DEVELOPMENT STRATEGY REVIEWED FROM AN ISLAMIC PERSPECTIVE - Siregar, Gustina; Putra, Yudha Andriansyah; Sabri, Tio Ardhito (Proceeding International Seminar of Islamic Studies, 2024)
Simalungum Regency, Tigga Runggu District is one of the areas that has the potential for economic excellence in the form of natural resource wealth to be developed, namely the horticultural agricultural sector which has an important role in supplying adequate nutrition for the community, especially oranges with high vitamin C content, but this high potential is not supported by easy access to increase farmers' production and income with strategic planning from an Islamic perspective. This research is quantitative. Researchers will describe the situation in the field to find a strategy formulation for developing the contribution of horticultural farming businesses using SWOT analysis. From the results of the Internal Factors Analysis Summary (IFAS) and External Factors Analysis Summary (EFAS) quadrant analysis, it is clear that